PENGARUH KOMPENSASI, NEPOTISME DAN KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN HOTEL DI KABUPATEN PINRANG - Yuslang, Muh Iqbal (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to describe and analyze the influence of compensation, nepotism, and leadership on the work motivation of hotel employees in Pinrang Regency. The data collection techniques used in this study were questionnaires and observation. The object of this research is 6 (six) hotels in Pinrang Regency with a total population of 96 respondents. The data analysis technique in this study used multiple linear regression analysis. Based on the results of the research that has been done, it shows that: 1) compensation has a positive and significant effect on the work motivation of hotel employees in Pinrang Regency. 2) nepotism has no significant negative effect on the work motivation of hotel employees in Pinrang Regency. 3) leadership has a positive and significant effect on the work motivation of hotel employees in Pinrang Regency.